Peran Generasi Z dalam Memperkuat Integrasi Nasional melalui Pemanfaatan Teknologi Digital di Kota Pematangsiantar - Limbong, Daniel Isar Valentino; Pardede, Kevin Rasi Dauly; Simangunsong, Joshua; Sidabutar, Hans Lambertus; Banjarnahor, Daulat Nathanael (Pancasila and Civics Education Journal, 2025)
ABSTRACTThis study aims to analyze the contribution of Generation Z in enhancing national integration by leveraging digital technology in the city of Pematangsiantar. Using a descriptive quantitative method, this research involved 60 participants consisting of students aged between 12 and 24 years old. Data was collected through a questionnaire using a Likert scale to measure two main variables: the frequency of digital technology use and awareness of national values. The findings indicate that Generation Z actively uses digital media not only for entertainment and communication but also to express social aspirations and build constructive national narratives. Most respondents demonstrated good digital literacy, engagement in online activities related to nationalism, and positive attitudes toward ethnic, religious, and cultural diversity. Social media platforms such as Instagram, TikTok, and YouTube are used to reinforce pride in national identity and enhance social solidarity. However, challenges such as the spread of false information, verbal hatred, and unequal access to technology remain significant obstacles. This study emphasizes the importance of digital literacy training and the creation of positive content that reinforces the values of national unity. These findings provide significant evidence that Generation Z possesses the strategic ability to serve as agents of national unity through creative, inclusive, and critical digital approaches. Keywords: Generation Z; National Integration; Digital Technology; Digital Literacy; Social Media. ABSTRAKStudi ini bertujuan untuk menganalisis kontribusi Generasi Z dalam meningkatkan integrasi nasional dengan memanfaatkan teknologi digital di Kota Pematangsiantar. Dengan metode kuantitatif deskriptif, penelitian ini melibatkan 60 peserta yang terdiri dari pelajar dan mahasiswa berusia antara 12 hingga 24 tahun. Data diperoleh melalui kuesioner yang menggunakan skala Likert untuk mengukur dua variabel utama: frekuensi pemanfaatan teknologi digital dan kesadaran terhadap nilai-nilai kebangsaan. Temuan menunjukkan bahwa Generasi Z dengan aktif memanfaatkan media digital bukan hanya untuk hiburan dan komunikasi, tetapi juga untuk mengekspresikan aspirasi sosial serta membangun narasi kebangsaan yang konstruktif. Sebagian besar responden memperlihatkan tingkat literasi digital yang baik, keterlibatan dalam aktivitas online yang berkaitan dengan nasionalisme, serta sikap positif terhadap keberagaman etnis, agama, dan budaya. Media sosial seperti Instagram, TikTok, dan YouTube digunakan untuk meneguhkan rasa bangga akan identitas bangsa dan meningkatkan solidaritas sosial. Meski begitu, tantangan seperti penyebaran informasi palsu, kebencian verbal, dan ketidakmerataan akses teknologi tetap menjadi rintangan yang berarti. Studi ini mengusulkan pentingnya pelatihan literasi digital dan penciptaan konten positif yang memperkuat nilai-nilai persatuan bangsa. Hasil ini merupakan bukti signifikan bahwa Generasi Z memiliki kemampuan strategis sebagai agen penyatuan nasional melalui pendekatan digital yang kreatif, inklusif, dan kritis.Kata Kunci: Generasi Z; Integrasi Nasional; Teknologi Digital; Literasi Digital; Media Sosial.